Clinical and Basic Immunodermatology - Gaspari, Anthony A.; Tyring, Stephen K.; Kaplan, Daniel H. (Springer International Publishing : Imprint: Springer, 2017)
This book is an in-depth and user-friendly reference for better understanding immune-mediated skin diseases and their therapies. The focus is on the needs of the physician, resident, or student to understand the pathophysiology of the disease as well as the mechanisms of action of the therapies. Clinical and Basic Immunodermatology, Second Edition is an effective teaching tool that has practical applications for use on a daily basis. It is a valuable resource for practicing dermatologists, dermatology residents and students, and healthcare workers in related fields.
Keywords: Medicine.; Immunology.; Allergy.; Dermatology.; Infectious diseases.; elektronické knihy; electronic books